Fundamentals of investment project appraisal : (feasibility and viability studies) - Egho major (Lagos : Masam Publishers, 1991)
This edition examines the analytical appraisal, the fundamentals concept of investment cash flows including capital and revenue expenditure.
asm; 06/03/19
Loans
Keywords: Finance; Savings and Investment